Recurrent haemoptysis, left-sided chest pain and an evolving left lower lobe cavity in a 50-year old smoker with prior high ethanol intake. (22nd December 2011) - Taylor, Matthew; Butler, Claire; Lekkas, Anastasios; Kurukulaaratchy, Ramesh J
Abstract : The authors describe a case of pancreatico-pleural fistula that presented as recurrent pyogenic chest disease in a patient with underlying ethanol related pancreatic disease. The diagnosis was suspected, given the context of non-resolving chest sepsis despite repeated antibiotics in a patient with known pancreatic disease. Although not revealed by initial tests the diagnosis was confirmed by repeating imaging investigations. The fistula was repaired surgically with consequent resolution of chest disease without need for extensive thoracic surgery.